Implementation Of The Unified Approach Method In Design Of A Website Based School Information System SMK PAB 5 Klambir Lima School - Farida, Siti; Siregar, M. Furqon; Ruziq, Fahmi (Journal of Technology and Computer, 2024)
In the era of the times, all activities are done semi-online. In a sense, all activities can be done in 1 hand by utilizing technology (smartphone). Similarly, in presenting or explaining a product to the public, the delivery of information is not optimal if done with a paper presentation. It was found that the lack of maximum delivery of information to the public on products, or agencies that want to be introduced to the wider community. that you want to introduce to the wider community. This solution can be done by apply the technology of a website that is published to online media, mass media and other media. mass media and other media. It is hoped that with today's technology, the public can see whenever the information is disseminated. Information in the category of institutional profiles, new student admissions, and activities that are intuitive and dynamic. intuitive and dynamic.